2000
DOI: 10.1073/pnas.160105897
|View full text |Cite
|
Sign up to set email alerts
|

The nonpsychoactive cannabis constituent cannabidiol is an oral anti-arthritic therapeutic in murine collagen-induced arthritis

Abstract: The therapeutic potential of cannabidiol (CBD), the major nonpsychoactive component of cannabis, was explored in murine collagen-induced arthritis (CIA). CIA was elicited by immunizing DBA͞1 mice with type II collagen (CII) in complete Freund's adjuvant. The CII used was either bovine or murine, resulting in classical acute CIA or in chronic relapsing CIA, respectively. CBD was administered after onset of clinical symptoms, and in both models of arthritis the treatment effectively blocked progression of arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
428
4
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 580 publications
(469 citation statements)
references
References 40 publications
18
428
4
7
Order By: Relevance
“…Although stimulation of VR1 receptors leads to vasodilation and in¯ammation, capsaicin and its long chain analogues exert anti-in¯ammatory e ects by rapidly desensitizing VR1 receptors to the action of nociceptive stimuli and causing depletion of sensory vasoactive neuropeptides (Szallasi & Blumberg, 1999). CBD also induces anti-in¯ammatory e ects, a possible explanation for this property being its capability of modulating the release of anti-in¯ammatory or pro-in¯ammatory mediators (Srivastava et al, 1998, Malfait et al, 2000. CBD and capsaicin also have in common anti-convulsive and anti-rheumatoidarthritis e ects (Consroe et al, 1981;Dib & Falchi, 1996;Malfait et al, 2000;Lorton et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although stimulation of VR1 receptors leads to vasodilation and in¯ammation, capsaicin and its long chain analogues exert anti-in¯ammatory e ects by rapidly desensitizing VR1 receptors to the action of nociceptive stimuli and causing depletion of sensory vasoactive neuropeptides (Szallasi & Blumberg, 1999). CBD also induces anti-in¯ammatory e ects, a possible explanation for this property being its capability of modulating the release of anti-in¯ammatory or pro-in¯ammatory mediators (Srivastava et al, 1998, Malfait et al, 2000. CBD and capsaicin also have in common anti-convulsive and anti-rheumatoidarthritis e ects (Consroe et al, 1981;Dib & Falchi, 1996;Malfait et al, 2000;Lorton et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…CBD also induces anti-in¯ammatory e ects, a possible explanation for this property being its capability of modulating the release of anti-in¯ammatory or pro-in¯ammatory mediators (Srivastava et al, 1998, Malfait et al, 2000. CBD and capsaicin also have in common anti-convulsive and anti-rheumatoidarthritis e ects (Consroe et al, 1981;Dib & Falchi, 1996;Malfait et al, 2000;Lorton et al, 2000). Here we found that CBD, compared to capsaicin, is a full, although weak, agonist of human VR1 at concentrations that might be (4) Cannabidiol, VR1 receptors and anandamide inactivation T. Bisogno et alattained after administration of this compound at the doses often used in vivo (10 ± 50 mg kg 71 in men), and lower than those required for CBD to bind to cannabinoid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THC induces apoptosis in macrophages (Zhu et al, 1998). Cannabidiol causes a dose-dependent suppression of lymphocyte proliferation (Malfait et al, 2000). D 8 -THC, CP55940, and anandamide also suppress T-and B-cell proliferation (Schwarz et al, 1994).…”
Section: Proliferation and Chemotaxismentioning
confidence: 99%
“…2-AG increases NO in human monocytes, and this is blocked by SR141716A, but not SR144528 (Stefano et al, 2000). 2-AG does not alter NO from mouse macrophages (Gallily et al, 2000). Why plant and synthetic cannabinoid agonists induce the opposite response to endocannabinoids is an open question.…”
Section: No Productionmentioning
confidence: 99%